Preparation of Poly (Hydroxamic Acid) from Poly (Styrene-co-Methyl Metha Acrylate) and the Study of the use of Water Purification of Heavy Metal Elements - Noor Fakhrie Mohammed (Journal of Global Pharma Technology, 2019)
In this study, the poly (styrene-co-Methyl metha acrylo hydroxamic acid) was prepared from the poly(styrene-co-methyl metha acrylate) which prepared by free radical polymerization using the benzoyl peroxide initiator to co- polymerization between (methyl metha acrylate) and (styrene) at atemperrature 70 ⁰C a mixing ratio (1:1) a conversion rate 20% and then conversion the polymer output to poly (hydroxamic acid) by reacting with hydroxyl amine hydrochloride in a strong base medium using potassium hydroxide with thermal escalation for 48 hours. The resulting poly (hydroxamic acid) and poly (styrene-co-Methyl metha acrylate) were identified by the FT-IR spectra. An adsorption study of heavy metal ions such as Fe3+, Cu2+, Co2+and pb2+ by poly (hydroxamic acid) was done. The effects of time, temperature and an acid function on adsorption ions were also studied. Calculation of desorption temperature of the metallic ions at two thermal degrees 10, 20 ⁰C shows that adsorption is chemical type.Keywords: Hydroxamic acid, Poly Hydroxamic acid, heavy metals, Adsorption.